Method for in vivo observation of karyokinesis of the somatic nucleus of Neurospora and Gelasinospora species - J. Weijer (Fungal Genetics Reports, 1965)
Method for in vivo observation of karyokinesis of the somatic nucleus of Neurospora and Gelasinospora species